Sigmoid volvulus in pregnancy: Case report and literature review - Tarik Souiki; Tayeb Ouazzani; Badreeddine Alami; Ahmed Zerhouni; Karim Ibn Majdoub; Imane Toughrai; Khalid Mazaz (Formosan Journal of Surgery, 2022)
Sigmoid volvulus in pregnancy is a rare but potentially serious condition. It is related to a high risk of maternal and fetal morbidity and mortality. This is mainly due to delayed diagnosis and treatment. We report the case of a 38-year-old multiparous patient, pregnant at 32 weeks of gestation, who presented to the emergency room with intestinal obstruction evolving for 2 days. At the emergency room, radiological exploration revealed a sigmoid volvulus. Endoscopic decompression was unsuccessful. A midline laparotomy was performed urgently revealing a necrotic sigmoid colon. A sigmoidal resection with a colostomy (Hartmann's procedure) was performed. In utero, fetal death occurred intraoperatively. The patient was transferred to the intensive care unit. Induction of labor was performed on the 2nd postoperative day with vaginal delivery of a stillborn. Recovery was good with the restoration of intestinal continuity 4 months later. Through this case and a review of recent literature, we discuss the diagnostic and therapeutic difficulties of this rare entity and highlight the seriousness of delay in the management of this surgical emergency.